Israeli identity : in search of a successor to the pioneer, Tsabar, and settler - Weissbrod, Lilly, 1929- (Oxon, OX : Routledge, 2013)
This thoroughly researched book reveals the true identity of the modern Israeli. Israelis are unique in having changed their identity three times in only one hundred years. Written in a user-friendly style, the book will appeal to scholars and students of the Middle East.
Cover; Half Title; Series Page; Title Page; Copyright Page; Dedication; Table of Contents; Introduction; 1 The Pioneer: An Ambivalent Identity; 2 The Tsabar: A Self-Defensive Identity; 3 The Erosion of the Tsabar Identity; 4 The Settler: A Quasi-Religious Identity; 5 Blurry Boundaries; 6 Fracture; 7 Concluding Remarks; Epilogue; Bibliography; Index.
Print version record.
Includes bibliographical references (pages 243-254) and index.
English.
eBooks on EBSCOhost
Keywords: Jews -- Israel -- Identity; Self-perception -- Israel; National characteristics, Israeli; Israel -- Social conditions -- 20th century; Juifs -- Israël -- Identité.; Perception de soi -- Israël.; Israéliens.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Jews -- Identity; National characteristics, Israeli; Self-perception; Social conditions; Israel; 1900-1999